Foreword: Proceedings From the First Annual Lumbar Total Disc Replacement Summit. (15th December 2017) - Blumenthal, Scott; Buttermann, Glenn; Garcia, Rolando; Gornet, Matthew; Grunch, Betsy; Guyer, Richard; Janssen, Michael; Kimball, Brent; Lewis, Adam; Mesiwala, Ali; Miller, Lynn; Morreale, Joseph; et al.
Abstract : N/A: This publication focuses on proceedings from the First Annual Lumbar Total Disc Replacement Summit, held October 25, 2016 in Boston, MA. The Summit brought together 17 thought leading surgeons who employed a modified-Delphi method to determine where consensus existed pertaining to the utilization of lumbar total disc replacement as a standard of care for a subpopulation of patients suffering from degenerative disc disease.